2014
DOI: 10.1016/j.molonc.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to ionizing radiation by targeting the homologous recombination pathway in glioma initiating cells

Abstract: Glioblastoma is deemed the most malignant form of brain tumour, particularly due to its resistance to conventional treatments. A small surviving group of aberrant stem cells termed glioma initiation cells (GICs) that escape surgical debulking are suggested to be the cause of this resistance. Relatively quiescent in nature, GICs are capable of driving tumour recurrence and undergo lineage differentiation. Most importantly, these GICs are resistant to radiotherapy, suggesting that radioresistance contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 55 publications
(83 reference statements)
3
46
1
1
Order By: Relevance
“…It is well known that glioma cells have significant proliferation ability and a low apoptosis rate, as well as a powerful resistance to chemotherapy, radiation and biological treatment (13)(14)(15). These characteristics contribute to the malignant growth of tumors and may be a key reason for the recurrence of glioma (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that glioma cells have significant proliferation ability and a low apoptosis rate, as well as a powerful resistance to chemotherapy, radiation and biological treatment (13)(14)(15). These characteristics contribute to the malignant growth of tumors and may be a key reason for the recurrence of glioma (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that targeting RAD51 using small interfering RNA-radiosensitized established glioma cell lines, and recent data confirm that targeting HR is more effective at radiosensitizing GSCs than inhibiting the major alternative DSB repair pathway, non-homologous end-joining (NHEJ) (Lim et al., 2014, Short et al., 2011). Inhibition of HR can be achieved through modulating expression, inhibiting nuclear translocation, or preventing DNA binding of RAD51, and small-molecule inhibitors have been developed, including B02 and RI-1.…”
Section: Introductionmentioning
confidence: 95%
“…Inhibition of DNA repair improves the radiosensitivity of GSCs (27). Hyperthermia is thought to act as a radiosensitizer primarily by interference of DNA damage repair (28).…”
Section: Resultsmentioning
confidence: 99%